Analysis of first-year university students' conceptual understanding of direct current electric circuits - Judyanto Sirait (Universitas PGRI Pontianak, 2026)
The concept of direct current (DC) electricity is taught from elementary school through higher education. The concepts covered include electric current, voltage (potential difference), and electric circuits in series and parallel configurations. However, students often experience difficulties in understanding these concepts, and such misconceptions frequently persist into university education. Therefore, this study aimed to analyze first-year university students’ conceptual understanding of direct current electric circuits. A descriptive survey with qualitative explanation was employed to investigate students’ conceptions in depth, involving 107 participants. Students completed multiple-choice questions and were asked to provide written explanations for each selected answer. The analysis revealed that more than 50% of the students were unable to answer the questions correctly. Most students believed that a battery is a constant source of electric current. In addition, many students assumed that adding more batteries would always increase the voltage regardless of the battery configuration. Furthermore, students demonstrated difficulties in understanding the behaviour of bulbs in series and parallel circuits. These findings indicate that first-year university students hold significant misconceptions related to direct current electricity. Therefore, educators need to implement instructional approaches that effectively support students in constructing scientifically accurate concepts of DC electric circuits.